The influence of usefulness, adequacy of information, and perceived risk of electronic money Brizzi adoption in Banda Aceh – Indonesia - Muslim A Djalil; Muhammad Arfan; M Rizal Yahya; Nura Sahirah (Proceedings of AICS - Social Sciences, 2017)
The objective of research is to investigate the influences of usefulness, the adequacy of information, and perceived risk on the electronic money adoption Brizzi in Banda Aceh. The object of this study is Bank customers in Banda Aceh city who use e-money services of which consist of 100 persons. The research employs purposive sampling method and taken by using Slovin’s formula. This field survey based research is mainly based on primary data obtained directly from a closed questionnaires distributed to respondents. The data collected are analyzed by using multiple regression method with SPSS software. The results of this research show that usefulness, the adequacy of information, and perceived risk have a significant influence on the electronic money adoption Brizzi in Banda Aceh, either tested partially or simultaneously